“They organised our exploitation”: women workers and class consciousness in Tomasa Cuevas's testimonial work (Anclajes, 2026)
The extensive testimonial work collected by Tomasa Cuevas in her three volumes, Cárcel de mujeres (1939-1945), Cárcel de mujeres and Mujeres de la resistencia, has established itself as a primary source for the study of women´s prison cultures. At the same time, these texts are the repository of workers´ memories that are revealed through the self-consciousness of belonging to the working class and the expression of a diversity of tasks, activities and experiences lived and carried out by them. In this paper, we will analyse the way in which these female working-class cultures are manifested in Cuevas´s work, both in terms of the impact of affective bonding and the direct experience of social inequality on class consciousness, and in terms of prison socialisation and its contribution to the consolidation of a series of social relations in which the category of class is central.
Keywords: Tomasa Cuevas; Testimonial writing; Class consciousness; 20th Century; Francoist Spain